A terminologia náutica no diccionario da lingua brasileira de Luiz Maria da Silva Pinto - Regina Celia Esteves dos Santos Tormin Botelho (2011)
This paper aims the study of nautical terms contained in the Brazilian Language Dictionary (Diccionario da Lingua Brasileira) (DLB), Luiz Maria da Silva Pinto. It was published in Ouro Preto in Minas Gerais at Typography Silva, in 1832, ten years after the proclamation of the independence of Brazil. This dictionary is now considered the first printed dictionary in that country. Its size is small but there are 1111 pages in the current pattern of a "portable dictionary". The DLB is a rare book. In the presented study we have used the volume in digital format of the microfilm edition undertaken by the Arquivo Público Mineiro that is located in the capital of Minas Gerais, Belo Horizonte. At first we surveyed the lexical words referring to the world of navigation noting the "tags of use" which refers to nautical terminology. We started the paper from a dicitionary corpus of nautical terminology, composed of 153 terms, consisting of 117 nouns, 03 adjectives, 32 verbs and an adverb. In a second step, the data were arranged in lexicographic forms. In each of the words we wrote a lexical form that shows us if the word was used or not in Brazil since the colonial era to the present day besides showing the origins and other important information for linguistic analysis. We based ourselves on Haensch, Biderman, Krieger and Finatto for the concepts of lexicon and lexicology and on Barros for the Terminology. For data analysis we took as the basis guiding the development of Historical Linguistics as presented by Cohen and Bynon. As we started from nautical terminology we worked towards the concept to word" similar to the method onomasiological. Next, we extended our analysis to the word or the sign language - a route semasiology. Our analysis revealed an European terminology and unrepresentative of the Brazilian maritime context, rather descriptive and prescriptive.